Media Sosial Instagram Sebagai Tempat Untuk Personal Branding Seorang Selebgram - Alisha Febylania; Siti Nursanti; Flori Mardiani Lubis (Jurnal Ilmiah Wahana Pendidikan, 2022)
Now days, social media is not just a medium for communicating and interacting, but can also act as a place for someone's personal branding efforts. One of the several social media currently available, which is being used as a place to do personal branding, is Instagram. Instagram itself is an application that allows users to share photos and videos. From one of these social media, the term celebgram was born which allows them to make personal branding efforts in it. The purpose of this study is to find out how personal branding is carried out by celebrities on Instagram social media. This study uses descriptive qualitative with descriptive research type. This data collection technique consists of in depth interview and observation. The results of the study also show that the personal branding carried out by the celebrity in this study has harmony between what he shows on his Instagram account and his real life, or in other words it can be called authentic. In addition, in addition to the personal branding activities that are carried out, the celebrities in this study also interact with their followers through the features available on Instagram.